2022
DOI: 10.3389/fendo.2022.890053
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bone Mineral Density in US Adults With Diabetes, Prediabetes and Normoglycemia From 2005 to 2018

Abstract: BackgroundAccumulating evidence has shown that diabetes has an impact on bone metabolism with conflicting results. Furthermore, little is known about the relationship of prediabetes with bone mineral density (BMD). Therefore, we explored the association between BMD and glucometabolic status in adults in the US.MethodsIn this cross-sectional study, we extracted and analyzed data from the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018. A total of 14610 subjects aged 40 ≥ years diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Previous cross-sectional studies had reported higher BMD in people with T2DM compared with individuals without diabetes ( 4 6 ). The findings from our prospective POP-ABC study demonstrate a similar association between BMD and prediabetes, consistent with previous findings from cross-sectional surveys ( 19 , 20 ). Exploring possible mechanisms, we observed significant correlations between baseline BMD and measures of adiposity and glucose tolerance (2hPG) among our study participants.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous cross-sectional studies had reported higher BMD in people with T2DM compared with individuals without diabetes ( 4 6 ). The findings from our prospective POP-ABC study demonstrate a similar association between BMD and prediabetes, consistent with previous findings from cross-sectional surveys ( 19 , 20 ). Exploring possible mechanisms, we observed significant correlations between baseline BMD and measures of adiposity and glucose tolerance (2hPG) among our study participants.…”
Section: Discussionsupporting
confidence: 91%
“…In one report, based on data from the U.S. National Health and Nutrition Examination Surveys (NHANES) from 2005 to 2014, adults 40 years of age or older with prediabetes had higher BMD but greater hip fracture risk compared with adults with normal glucose tolerance ( 19 ). In another cross-sectional study (based on NHANES 2005-2018 data), there was an increasing trend of BMD at the hip, femoral neck, and lumbar spine across the glycemic spectrum from normoglycemia, prediabetes, to diabetes in adults aged 40 years or older ( 20 ). However, these cross-sectional observations do not reveal the direction of the association between BMD and diabetes or prediabetes, nor do they permit causal inferences.…”
Section: Introductionmentioning
confidence: 99%
“…In the subgroup analysis, we found that the negative association between FPG trajectory and osteoporosis risk was significant in women. This corresponded with the study conducted by previous studies ( 9 , 25 ). Moreover, we found the significant association only existed among premenopause women.…”
Section: Discussionsupporting
confidence: 91%
“…“Hypertension” was defined as having an SBP ≥ 140 or/and DBP ≥90 mmHg or a history of hypertension [ 30 ]. Diabetes status was confirmed when the participants had a positive history of diabetes and/or elevated glycosylated hemoglobin (HbA1c) > 6.5% [ 31 ].…”
Section: Methodsmentioning
confidence: 99%